AMALAN AKHLAK KEPALA SEKOLAHDASAR ISLAM DI MALANG MELALUI MURAQABAH, MUHASABAH DAN MUJAHADAH - Triyo Supriyatno; Wan Mamat (Universitas Muhammadiyah Malang, 2019)
Muhasabah is a surveillance system involving the internal control process to ensure al- amr al-ma’ruf wa al-nahyu ‘an al-munkar implemented in Islamic education. The main purpose of this article is to examine the determinants of akhlak practices through elementary Islamic Education among Two Principal Schools. We’re collected data by non-participant observations, semi-structured interviews, documentation and principals’ journals. The results of this study showed that the practice of akhlak principals of Elementary Islamic School in Malang through muraqabah (behavioral observation), muhasabah (reflection practice) and Mujahadah (struggle of desires) contributed to the realization of the national education philosophy to produce a generation of school community who are righteous knowledgeable, competent, honorable and contribute to a universalcivilization.